Contextual Effect of Village, Implementation of Theory of Planned Behavior, and Decision to Quit Smoking: A Multilevel Analysis - Rajba Nazalah; Argyo Demartoto; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Behavior is determined by the intention to perform a behavior. Intentions are further influenced by three constructs, attitudes (the advantages and disadvantages of engaging in a behavior), subjective norms (social influences on a behavior) and perceived behavioral control (facilitators and barriers to a behavior). The study aimed to analyze the contextual influence of the hamlet on the application of the Theory of Planned Behavior (TPB) construct in the decision to stop smoking among adults in Surakarta. Subjects and Method: A cross-sectional study was conducted in 22 villages in Surakarta in November-December. A sample of 200 adult smokers and quitters was selected using snowball sampling. The dependent variable is the decision to stop smoking. The independent variables are intention, attitude, subjective norm, and perceived behavioral control. Data were collected by questionnaire and analyzed using multilevel multiple linear regression. Results: A person's decision to stop smoking is directly influenced by the intention to stop smoking (b= 0.18: 95% CI= 0.07 to 0.28; p= 0.001). Intention to quit smoking was significantly influenced by attitudes about smoking (b= 0.21: 95% CI= 0.10 to 0.32; p <0.001), subjective norms (b=0.19: 95% CI= 0.06 to 0.32; p= 0.003), and perception behavioral control (b= 0.25: 95% CI= 0.09 to 0.42; p= 0.002). Variations at level 2 hamlets have a contextual relationship to the decision to stop smoking (ICC= 10.43%). Conclusion: Decision to quit smoking is directly influenced by the level of intention to quit smoking. Intention to quit smoking itself is influenced by attitudes, subjective norms, and perceived behavioral control. Hamlet has a contextual effect on the decision to quit smoking.